The pollution effect on the denitrifying capacity of methanogenic sludges. (19th December 2022) - Camacho-López, Cesar; Romo-Gómez, Claudia; Otazo-Sánchez, Elena; Gómez Aldapa, Carlos A.; García-Nieto, Edelmira; Juárez-Santacruz, Libertad
Abstract: The denitrification process has been studied for biodegradation of some emerging contaminants (ECs). For this, anaerobic sludges from different Wastewater Treatment Plants (WTP) have been used; however, the biodegradation capacity can differ due to the contact they have had with various pollutants, given their origin. This work aims to evaluate the kinetic and metabolic capacity of two denitrifying sludges from different WTPs to biodegrade CH3 COO − -C and NO3 − -N. Denitrifying tests were carried out in batches with CH3 COO − -C (30 mg L −1 ) in a CN −1 relationship of 1.8 with sludge from a WTP of an educational center (WTP-A) and CH3 COO − -C (50 mg L −1 ) to a CN −1 of 1.4 with another from the WTP of Atotonilco de Tula, Hidalgo, México (WTP-B). The results showed that the biodegradation rate of CH3 COO − -C and NO3 − -N with the WTP-B sludge was 35 and 75% greater, respectively, compared to the WTP-A sludge. Therefore, we suggest that the consumption difference of substrate is attributable to the sludges of WTP, which have been exposed to a high concentration of a great variety of pollutants. HIGHLIGHTS: The metabolism and kinetics of two denitrifying sludges of different origins were compared. Assays were carried out in batches with CH3 COO − -C as the donor of electrons and NO3 − -N as the acceptor. Biodegradation rates from WTP-B sludge were higher than the WTP-A's rates. The previous exposure to pollutants showed its high influence in the metabolic capacity and denitrifying rate of WTP-B sludge. The C/N relationship is not a factor that influences in the kinetics of the process in both sludges. Graphical Abstract